The Role of Religious Activists in Stopping Violence and Bridging the Gap in Areas of Ethnic Conflict in Nigeria - Samuel, Omawunmi (Journal of Philosophy, Culture and Religion, 2023)
Purpose: The purpose of this study was to evaluate various approaches used by the religious peace makers and organizations and factors which hinder their effectiveness in peace building and reconciliation in Nigeria. Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low-cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Results: The results revealed that there exist conceptual and contextual gaps relating to the study on various approaches used by the religious peace makers and organizations and factors which hinder their effectiveness in peace building and reconciliation in Nigeria. Preliminary empirical review reveals that. religious methods such as problem solving workshops, mediations and negotiations and confessions have been very effective in peace building and reconciliation. However, the study established that the religious approaches are not applied continually so as to promote peace and reconciliation. Unique Contribution to Theory, Practice and Policy: Human needs theory and reconciliation theory, may be used in peace building and reconciliation. The results of this research will enrich the canon of writing on conflict resolution and rapprochement already present in West African universities' Departments of Philosophy and Religious Studies.